2016
DOI: 10.1186/s12906-016-1252-4
|View full text |Cite
|
Sign up to set email alerts
|

Antidiarrheal activity of crude methanolic root extract of Idigofera spicata Forssk.(Fabaceae)

Abstract: BackgroundTill now many of medicinal plants having claimed therapeutic value traditionally are waiting scientific verification of their efficacy and safety. Accordingly this study is conducted to evaluate the antidiarrheal activity of hydromethanolic root extract of Indigofera spicata Forssk. in castor oil induced diarrhea model, misoprostol induced secretion model and its antimotility activity using charcoal as a marker.MethodsIn all the three models the animals were randomly allocated into five groups of six… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
34
0
4

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(40 citation statements)
references
References 34 publications
2
34
0
4
Order By: Relevance
“…Phytochemical screening study showed that the leaves extract of Ruta chalepensis was endowed with alkaloids, flavonoids, polyphenols, terpenoids, cardiac glycosides, and saponins. [22] Previous studies showed that terpenoids and steroids like phytosterols have a capacity to inhibit the production of prostaglandin E2 [23,24], which has a crucial role in the stimulation of intestinal secretions. [25,26] Accordingly, the significant antidiarrheal activity observed in the Ruta chalepensis crude extract at different doses could probably be linked to the presence of these secondary metabolites in the crude extract.…”
Section: Discussionmentioning
confidence: 99%
“…Phytochemical screening study showed that the leaves extract of Ruta chalepensis was endowed with alkaloids, flavonoids, polyphenols, terpenoids, cardiac glycosides, and saponins. [22] Previous studies showed that terpenoids and steroids like phytosterols have a capacity to inhibit the production of prostaglandin E2 [23,24], which has a crucial role in the stimulation of intestinal secretions. [25,26] Accordingly, the significant antidiarrheal activity observed in the Ruta chalepensis crude extract at different doses could probably be linked to the presence of these secondary metabolites in the crude extract.…”
Section: Discussionmentioning
confidence: 99%
“…Constipation and diarrhea are two distinct antagonistic disorders characterized by an imbalance in intestinal absorption/secretion leading to unexplained abdominal pain, discomfort and bloating in association with altered bowel habits (Birru and others ).…”
Section: Discussionmentioning
confidence: 99%
“…Statistical significance of differences between groups was assessed by one-way ANOVA followed by post-hoc Tukey's multiple comparison test. The results were considered significant at p-value < 0.05 [18][19].…”
Section: Methodsmentioning
confidence: 99%